Epistemological beliefs in mathematics teacher educators: An exploratory study in Chile - Mirko Aguilar-Valdés; Helena Montenegro (Journal of Pedagogical Research)
In Chile, mathematics results are insufficient at the school level. To address this problem, the need to rethink teaching has been raised. Evidence indicates that epistemological beliefs are at the basis of pedagogical decisions, and their study has been developed mainly in primary and secondary school teachers. However, scientific evidence is scarce regarding this belief in teacher educators. To fill this knowledge gap, this study aims to analyze the epistemological beliefs in mathematics teacher educators’ discourse. This research was developed using a qualitative approach. Seven teacher educators participated, and data was collected through a semi-structured interview. In the discourse of the teacher educators, a developed tendency is observed in each dimension of their epistemological beliefs. However, links between this type of belief and some specific context characteristics are noticed. It is suggested that spaces for dialogue and reflection within the academic staff be implemented to analyze their epistemological beliefs and promote their development among future teachers.